Tropical Deltas and Coastal Zones: Food Production, Communities and Environment at the Land and Water Interface 2010
DOI: 10.1079/9781845936181.0166
|View full text |Cite
|
Sign up to set email alerts
|

The right rice in the right place: systematic exchange and farmer-based evaluation of rice germplasm for salt-affected areas.

Abstract: Traditional approaches for introducing improved rice varieties to farmers have demonstrated significant impact in favourable ecosystems in Asia, but with limited success in unfavourable ecosystems, as in saltaffected areas. Developing rice varieties with wider adaptation and broader tolerance of prevailing stresses is more viable for these areas, where abiotic stresses are particularly variable and complex, and growing conditions are too risky to persuade farmers to invest in inputs. The Challenge Program on W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The relatively low correlation in preference criteria between farmers and researchers during both wet and dry seasons indicated that farmers often had different priorities than the researchers, as also reported before ( Singh et al, 2010 ). Farmers’ preferences and their reasoning are important criteria for breeders to consider when developing new varieties to ensure they will be acceptable by farmers and adapted to local conditions.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The relatively low correlation in preference criteria between farmers and researchers during both wet and dry seasons indicated that farmers often had different priorities than the researchers, as also reported before ( Singh et al, 2010 ). Farmers’ preferences and their reasoning are important criteria for breeders to consider when developing new varieties to ensure they will be acceptable by farmers and adapted to local conditions.…”
Section: Discussionsupporting
confidence: 53%
“…This concern is particularly highlighted by the weak correlation between the preference scores of all farmers and grain yield, with the latter being a central criterion in most breeding programs. Apparently, farmers consider yield when selecting their most preferred varieties, but also other traits necessary for their local farming conditions ( Joshi et al, 1997 , Mandal et al, 2002 , Manzanilla et al, 2011 , Singh et al, 2010 , Singh et al, 2014 , Singh et al, 2016 ). Site-specific characteristics other than grain yield are expressly important in the wet season, as reflected by the significant correlations with yield in fewer trials than in the dry season (Tables 4 and 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations